Facile Synthesis of Hierarchical MgCo2O4@MnO2 Core-Shell Nanosheet Arrays on Nickel Foam as an Advanced Electrode for Asymmetric Supercapacitors. Issue 2 (10th January 2020) - Teng, Yifei; Yu, Deyang; Li, Yingdi; Meng, Ya'nan; Wu, Yunpeng; Feng, Yi; Hua, Yingjie; Wang, Chongtai; Zhao, Xudong; Liu, Xiaoyang
Abstract : Ternary transition metal oxides (TTMOs) material has recently drawn significant interests to researchers, as a potential electrode material to advance the energy storage technology. In this paper, the hierarchical MgCo2 O4 @MnO2 core-shell nanosheet arrays (CNAs) were resoundingly fabricated on nickel foam using a simple solvothermal reaction and a calcination afterwards. The assembled MgCo2 O4 @MnO2 electrode had a specific capacity of 968.98 C g −1 under 1 mA cm −2 in a 1 M KOH solution. Additionally, two asymmetric supercapacitors (ASCs) were assembled, one with PVA-KOH gel (PKG) as electrolyte and the other with KOH solution as electrolyte. Both of the ASCs were made with MgCo2 O4 @MnO2 CNAs/Ni foam as the positive electrode and the activated carbon (AC) as the negative electrode, and both exhibited extraordinary electrochemical properties. The remarkable electrochemical performance revealed that the MgCo2 O4 @MnO2 nanomaterial was a prospective electrode material and can be applied potentially in energy storage field.